Inovasi Tes Maharah Kalam Berbasis penilaian Kurikulum Merdeka pada Buku durus Al- lughah Al- arabiyah Jilid 1 - Muhammad Sayuti; Tasha Ayu Azzahra; Sinta Purnama Sari (Jurnal Pelita Manajemen Pendidikan, 2024)
The purpose of the Independent Curriculum-Based Maharah Kalam Test Innovation is to provide students with an understanding of learning and be able to improve maharah kalam. The method in this study uses a descriptive qualitative approach. This research uses descriptive qualitative type, which describes and analyzes phenomena, social activities, attitudes, beliefs, perceptions, thoughts of people as well as individuals and groups. The results in this study are based on the researcher's analysis, the form of instructions in the table above is given repeatedly in each chapter. So that the Arabic language books have the same order of questions in each chapter, especially in the Maharha Kalam. The innovation provided by the researcher is the making of a Maharah Kalam test assessment using the Smart Apps Application. where in the application the researcher made Hiwar which was presented then immediately there was a question test related to Maharah Kalam which was written by the researcher.